1986
DOI: 10.1021/bi00363a040
|View full text |Cite
|
Sign up to set email alerts
|

Menadione-(2-methyl-1,4-naphthoquinone) dependent enzymic redox cycling and calcium release by mitochondria

Abstract: The results presented in this paper reveal the existence of three distinct menadione (2-methyl-1,4-naphthoquinone) reductases in mitochondria: NAD(P)H:(quinone-acceptor) oxidoreductase (D,T-diaphorase), NADPH:(quinone-acceptor) oxidoreductase, and NADH:(quinone-acceptor) oxidoreductase. All three enzymes reduce menadione in a two-electron step directly to the hydroquinone form. NADH-ubiquinone oxidoreductase (NADH dehydrogenase) and NAD(P)H azoreductase do not participate significantly in menadione reduction. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(44 citation statements)
references
References 22 publications
1
43
0
Order By: Relevance
“…We then examined whether the deficiency in OGG1 altered susceptibility to cell death caused by 2-methyl-1. 4-naphthoquinone (menadione), which produces ROS within cells (Supplementary Figure S2; Frei et al, 1986). The median lethal dose of menadione (LD 50 ¼18.5 mM) for Ogg1 À/À MEFs was significantly lower than that for the wild type (32 mM) ( Figure 1A).…”
Section: Ogg1mentioning
confidence: 99%
“…We then examined whether the deficiency in OGG1 altered susceptibility to cell death caused by 2-methyl-1. 4-naphthoquinone (menadione), which produces ROS within cells (Supplementary Figure S2; Frei et al, 1986). The median lethal dose of menadione (LD 50 ¼18.5 mM) for Ogg1 À/À MEFs was significantly lower than that for the wild type (32 mM) ( Figure 1A).…”
Section: Ogg1mentioning
confidence: 99%
“…We previously demonstrated that menadione caused similar substrate proteolysis (p53 and atypical PARP cleavage) in NQO1-deficient cells, or at high doses in cells that express NQO1 where detoxification processes were over-ridden (5). 3 The semiquinone form of menadione can undergo spontaneous oxidation to the parent quinone (59,63,65,66); a pattern similar to the futile cycling observed after ␤-Lap bioactivation by NQO1 (5). Loss of reducing equivalents, such as NADH, due to the futile cycling of menadione may cause inactivation of the electron transport chain with the concomitant loss of mitochondrial membrane potential, and thus, loss of ATP (67,68).…”
Section: Camentioning
confidence: 99%
“…To investigate in greater depth the involvement of free radical injury in the pathogenesis of the cardiomyopathy with cataracts and complex I deficiency, skin fibroblasts from a group of patients were assessed for hydroxyl radical production and aldehydic lipid peroxidation products with and without redox active agents known to cause cell injury by free radical-mediated mechanisms (18,19).…”
Section: Introductionmentioning
confidence: 99%